(untitled) (Physical Education, Health and Social Sciences, 2026)
Foodborne pathogens continue to pose a major global public health and economic burden, with traditional detection and control methods increasingly limited by delays, resistance development, and environmental concerns. This review explores the transformative role of microbial biotechnology in modern food safety management. Advanced culture-independent detection technologies including nucleic acid amplification (PCR, LAMP, RPA), next-generation sequencing (NGS)/metagenomics, nanotechnology-integrated biosensors (electrochemical, optical, SERS), and CRISPR-Cas-based diagnostics enable rapid, sensitive, specific, and often on-site identification of pathogens such as Salmonella, Listeria, and E. coli. For control, biologically targeted strategies are gaining prominence, including bacteriophage therapy for pathogen elimination and biofilm disruption, bacteriocins and protective cultures from lactic acid bacteria, and engineered CRISPR-Cas systems for precision microbial elimination. Synthetic biology further advances the field through precision fermentation for sustainable ingredient production and next-generation probiotics with diagnostic and therapeutic functions. Digital integration of artificial intelligence (AI), machine learning, IoT-based real-time monitoring, predictive microbiology, dynamic HACCP, and blockchain traceability shifts food safety toward predictive and preventive paradigms. The review also addresses the growing threat of antimicrobial resistance (AMR) in the food chain and advocates for One Health approaches, reduced antibiotic use, and alternative therapies. Despite technical, economic, regulatory, and societal challenges, microbial biotechnology offers sustainable, high-precision solutions to enhance food safety across the farm-to-fork continuum.